Strategi Komunikasi Pandawara Group dalam Program Adopsi Sungai - 10080021158, Ismi Hafizhah; Yulianti, S.Sos., M.Si. (Bandung Conference Series: Public Relations, 2025)
Abstract. This study aims to analyze the communication strategy carried out by Pandawara Group in implementing the Adopsi Sungai program as an effort to increase public awareness and involvement in environmental pollution issues, especially rivers. Pandawara Group is known as a young community that actively educates the public, especially in cleaning activities. This research uses a qualitative approach with a case study method. The five-step communication planning model is used as an analytical framework. The results show that Pandawara Group's communication strategy in the river adoption program goes through five stages. The first stage is research, identifying the main problems that occur in the downstream of the river, the second stage is planning by determining the coverage area and river criteria, the third stage is implementation, conducting formal and informal approaches with the community, then the fourth stage is evaluation, carried out every month or every six months and finally, the fifth stage, reporting the results of activities delivered openly through social media and stakeholders. Pandawara Group initiated the Adopt a River Program as a long-term solution to the problem of river pollution, which was previously only handled through clean-up actions in the #onedayonetrashbag campaign. Abstrak. Penelitian ini bertujuan untuk menganalisis strategi komunikasi yang dilakukan oleh Pandawara Group dalam mengimplementasikan program Adopsi Sungai sebagai upaya peningkatan kesadaran dan keterlibatan masyarakat terhadap isu pencemaran lingkungan, khususnya sungai. Pandawara Group dikenal sebagai komunitas muda yang aktif mengedukasi publik terutama dalam kegiatan bersih-bersih. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Model perencanaan komunikasi lima langkah digunakan sebagai kerangka analisis. Hasil penelitian menunjukan bahwa strategi komunikasi Pandawara Group dalam program adopsi sungai melalui lima tahap. tahap pertama yaitu penelitian, mengidentifikasi masalah utama yang terjadi di hilir sungai, tahap kedua yaitu perencanaan dengan menentukan cakupan wilayah dan kriteria sungai, tahap ketiga pelaksanaan, melakukan pendekatan formal dan informal dengan masyarakat, lalu tahap keempat evaluasi, dilakukan setiap bulan maupun setiap enam bulan dan terakhir, tahap kelima, pelaporan hasil kegiatan disampaikan terbuka melalui media sosial dan para stakeholder. Pandawara Group menginisiasi Program Adopsi Sungai sebagai bentuk solusi jangka panjang terhadap permasalahan pencemaran sungai, yang sebelumnya hanya ditangani melalui aksi bersih-bersih dalam kampanye #onedayonetrashbag.